Social cognition and quality of life in Huntington's disease - Eddy, Clare M.; Rickards, Hugh (Frontiers in Psychiatry, 2022)
Individuals with Huntington’s disease (HD) and their close others report difficulties with social interaction, and previous studies have shown that the areas of quality of life detrimentally impacted by HD include social and emotional domains. However, despite the finding that individuals with HD often exhibit difficulties on standard tests of social cognition, the relationship between such impairments and patients’ everyday life has remained largely unexplored. We used a range of tasks assessing empathy, emotion recognition and Theory of Mind, to investigate whether patients’ performance may predict quality of life within the social and emotional domains, while also accounting for broader cognitive function, behavioural changes, motor symptoms, disease stage and functional capacity. Poorer social functioning was predicted specifically by a reduced tendency to attribute intentionality while viewing social animations, in addition to emotional blunting and apathy, while role limitations due to emotional problems were predicted by personal distress, irritability and aspects of executive function. These findings highlight the potential impact of Theory of Mind impairment on quality of life in HD, and suggest that enhanced assessment of social cognition will offer unique insight into patients’ social function and related wellbeing.